Gas sensor based on MgO-ZnO porous hierarchical structure sensitive material, preparation method and application thereof

By modifying the semiconductor material with Mg element doping and modification, MgO-ZnO porous hierarchical structure sensitive materials were prepared, which solved the problems of insufficient sensitivity of existing sensors and high detection limit, and achieved high sensitivity detection of ethanol gas, with the lower detection limit reaching 0.1ppm.

CN119827584APending Publication Date: 2025-04-15JILIN UNIVERSITY
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411961739.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing oxide semiconductor sensors have insufficient sensitivity and high detection lower limit when detecting ethanol gas, making it difficult to meet the needs of high gas-sensitive response and low detection lower limit.

Method used

By doping and modifying the semiconductor material with Mg elements, MgO-ZnO porous hierarchical structure sensitive materials were prepared, and commercially available tube structure sensors were used, combining simple hydrothermal methods and calcining processes to improve the sensitivity and selectivity of the sensor.

Benefits of technology

It realizes high sensitivity detection for ethanol gas, with the lower detection limit reaching 0.1ppm. It is suitable for the detection of ethanol steam content in the environment and has important application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827584A_ABST
    Figure CN119827584A_ABST
Patent Text Reader

Abstract

The invention relates to a gas sensor based on an MgO-ZnO porous hierarchical structure sensitive material, a preparation method and an application of the gas sensor in detection of ethanol gas, and belongs to the technical field of semiconductor oxide gas sensors. The outer surface of the Al2O3 ceramic tube substrate is provided with two parallel and annular gold electrodes which are separated from each other, the nano sensitive material is coated on the outer surface of the Al2O3 ceramic tube and the gold electrodes, and the nichrome heating coil is arranged in the Al2O3 ceramic tube; and the nano sensitive material is an MgO-ZnO porous hierarchical structure sensitive material. According to the invention, Mg element doping modification is carried out on the semiconductor material, the sensitivity of the gas sensor is increased, the detection lower limit of the sensor is reduced, and the gas sensor has high sensitivity, good selectivity and low detection lower limit, can be used for detecting the content of ethanol steam in the environment, and has good application prospects. The practicability of the sensor in the field of gas detection is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of semiconductor oxide gas sensors, and in particular relates to a gas sensor based on MgO-ZnO porous hierarchical structure sensitive material, a preparation method and an application in detecting ethanol gas. Background Art

[0002] The harm of ethanol to the human body is mainly manifested in the inhibitory effect on the central nervous system. It first causes the central nervous system to be excited and then inhibits the central nervous system. Acute poisoning can be divided into four stages: excitement, hypnosis, anesthesia, and suffocation. Long-term exposure to high concentrations of ethanol can cause symptoms of nasal and eye mucosal irritation, as well as headaches, dizziness, fatigue, nausea, etc. It is well known that drunk driving is extremely harmful. According to the "Blood and Breath Alcohol Content Threshold and Inspection Standards for Vehicle Drivers (GB / T19522-2010)" of the People's Republic of China, the breath ethanol concentration of 20-80mg / 100mL (44-176ppm) is the concentration for driving under the influence of alcohol, and the breath ethanol concentration greater than 80mg / 100mL is the concentration for drunk driving. As a means of obtaining information, sensors have received widespread attention and application, so it is of great significance to develop ethanol gas sensors with high gas sensitivity response and low detection limit.

[0003] In fact, research on improving the sensitivity of oxide semiconductor sensors has been continuously deepened, especially the development of nanoscience and technology has provided a good opportunity to improve sensor performance. Studies have shown that the recognition function, conversion function and sensitive body utilization rate of gas-sensitive materials determine the sensitivity of oxide semiconductor sensors. The work described in this invention is to carry out experiments around the above three points to research and develop high-performance gas sensors. Summary of the invention

[0004] The purpose of the present invention is to provide a gas sensor based on MgO-ZnO porous hierarchical structure sensitive material, a preparation method and an application in detecting ethanol gas. The present invention increases the sensitivity of the gas sensor and reduces the detection limit of the sensor by doping and modifying the semiconductor material with Mg element, thereby promoting the practical application of the sensor in the field of gas detection.

[0005] The sensor of the present invention has not only high sensitivity, but also good selectivity and a low detection limit. The detection limit of the sensor is 0.1 ppm, and can be used to detect the ethanol vapor content in the environment. The present invention adopts a commercially available tubular structure sensor, which has a simple manufacturing process, a small size, and a low price, and is conducive to industrial mass production, so it has important application value.

[0006] The gas sensor based on the MgO-ZnO porous hierarchical structure sensitive material described in the present invention is composed of an Al2O3 ceramic tube substrate with two parallel, annular and mutually independent gold electrodes on the outer surface, a nano-sensitive material coated on the outer surface of the Al2O3 ceramic tube and the gold electrodes, and a nickel-chromium alloy heating coil placed in the Al2O3 ceramic tube; the nano-sensitive material is a MgO-ZnO porous hierarchical structure sensitive material, and is prepared by the following steps:

[0007] (1) Dissolve 5 mmol of zinc nitrate hexahydrate, 10 mmol of urea, 3.3 g of polyvinyl pyrrolidone (PVP-K30) and magnesium nitrate hexahydrate in 60-80 mL of deionized water and stir magnetically for 20-40 minutes; wherein the atomic ratio of magnesium to zinc is 0.05-0.10:1;

[0008] (2) transferring the mixture solution obtained in step (1) into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, reacting at 140-160° C. for 8-15 hours; after naturally cooling to room temperature, washing the reaction product with deionized water and anhydrous ethanol by centrifugation alternately for 5-8 times, and then drying in an air atmosphere at 70-90° C. for 20-30 hours;

[0009] (3) The product obtained in step (2) is heated to 450-550° C. at a heating rate of 2-3° C. / min in a muffle furnace, and then calcined for 3-5 hours to obtain a white powder, which is the MgO-ZnO porous hierarchical structure sensitive material.

[0010] The method for preparing a gas sensor based on the MgO-ZnO porous hierarchical structure sensitive material of the present invention comprises the following steps:

[0011] (1) 5-15 mg of MgO-ZnO porous hierarchical structure sensitive material was mixed with 0.1-0.3 mL of a mixed solvent of anhydrous ethanol and deionized water in a volume ratio of 1:1 to form a slurry, and a brush was used to apply the slurry on the outer surface of the Al2O3 ceramic tube substrate and the gold electrode to a thickness of 15-30 μm; the inner diameter of the Al2O3 ceramic tube was 0.7-0.9 mm, the outer diameter was 1.1-1.3 mm, and the length was 3.8-4.2 mm; the width of the gold electrode was 0.35-0.45 mm, the distance between the two gold electrodes was 0.4-0.6 mm, and two folded platinum wires with a length of 4-6 mm were led out from each gold electrode;

[0012] (2) calcining the Al2O3 ceramic tube coated in step (1) at 350-450°C for 1.5-3.0h, then passing a nickel-chromium alloy heating coil (50-60 turns) with a resistance value of 30-40Ω through the interior of the Al2O3 ceramic tube, controlling the current passing through the heating coil so that the sensor operates at a suitable temperature, and finally welding the platinum wire of the sensor and both ends of the nickel-chromium alloy heating coil to a indirectly heated hexagonal tube socket;

[0013] (3) Aging the device obtained in step (2) in an air environment at 180-220° C. for 6-8 days, thereby obtaining the gas sensor based on the MgO-ZnO porous hierarchical structure sensitive material.

[0014] The working principle of the sensor of the present invention is as follows:

[0015] When the gas sensor based on the MgO-ZnO porous hierarchical structure sensitive material is placed in the air, the oxygen molecules in the air will grab electrons on the surface of the sensitive material and react with O2 - , O - Or 2- The sensor exists in a depletion layer on the surface of the material, and the resistance increases. When the sensor contacts the gas ethanol to be measured at a certain appropriate temperature, the gas molecules will undergo a redox reaction with the adsorbed oxygen molecules, releasing electrons back to the sensitive material, thereby reducing the resistance of the sensitive material. Here we define the sensitivity of the sensor as S: S = R a / R g , where R a is the resistance of the sensitive material between the gold electrodes of the sensor in air, R g It is the resistance of the sensitive material between the gold electrodes of the sensor after contacting the target gas.

[0016] The gas sensor based on the MgO-ZnO porous hierarchical structure sensitive material prepared by the present invention has the following advantages:

[0017] (1) MgO-ZnO porous hierarchical structure sensitive materials can be synthesized by a simple hydrothermal method. The synthesis method is simple, low-cost and has good reproducibility;

[0018] (2) By adjusting the amount of Mg doping, the gas-sensing properties of ethanol were optimized and the sensitivity to ethanol was improved. The detection limit of the gas sensor for ethanol was low, and it has broad application prospects in terms of detection content.

[0019] (3) The commercially available tubular sensor is used. The device process is simple, the size is small, and it is suitable for mass production. Of course, the actual application is not limited to the use of tubular structure sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 : SEM photos of the samples of the comparative example, embodiment 1, embodiment 2 and embodiment 3 at different magnifications; wherein the magnification of the first column is 2000 times, the magnification of the second column is 10000 times, and the magnification of the third column is 30000 times;

[0021] Figure 2 : Transmission electron microscopy photos of Example 2, Figure ab is a TEM image, Figure c is a HRTEM image, and Figure d is a SAED image;

[0022] Figure 3 : Comparison of the sensitivity of the sensors prepared in the comparative example, embodiment 1, embodiment 2 and embodiment 3 to 100 ppm of 5 different gases at 250°C;

[0023] Figure 4 : The relationship curve between the sensitivity of the sensors prepared in the comparative example, embodiment 1, embodiment 2 and embodiment 3 to 100ppm ethanol gas and the operating temperature;

[0024] Figure 5 : Real-time sensitivity curve of the sensor prepared in Example 2 to ethanol gas of different concentrations at 250°C;

[0025] Figure 6 : Example 2 response recovery curve to 100 ppm ethanol gas at 250°C.

[0026] Figure 1 The scanning electron microscope photos of the samples of the comparative example, embodiment 1, embodiment 2 and embodiment 3. It can be seen that all samples are hierarchical structure microspheres composed of porous nanosheets, and the dispersion of these microspheres is very good. In addition, with the increase of Mg doping amount, the size of the microspheres is getting smaller and smaller, and the thickness of the nanosheets of the comparative example, embodiment 1, embodiment 2 and embodiment 3 measured in the figure are 46.6nm, 41.6nm, 36.3nm and 31.2nm respectively (the average of three or two data in the third column of the figure), indicating that with the increase of Mg doping amount, the thickness of the nanosheets of the sensitive material gradually decreases;

[0027] Figure 2 The transmission electron microscope photos of the samples of Example 2. In Figures ab, the prepared sensitive materials have a hierarchical structure of ~4 μm and microspheres of porous nanosheet structure, in Figure c, the lattice spacing of ZnO can be seen, and in Figure d, the diffraction rings of ZnO can be seen;

[0028] Figure 3This is a comparison chart of the sensitivity of the comparative example, Example 1, Example 2 and Example 3 to 100 ppm of 5 different gases at 250°C; it can be seen that all gas sensors show high sensitivity to ethanol, and the sensitivity to ethanol is much higher than the sensitivity to other gases, among which Example 2 achieves the highest sensitivity;

[0029] Figure 4 The relationship curves of the sensitivity of the comparative example, Example 1, Example 2 and Example 3 to 100ppm ethanol gas and the operating temperature are shown; it can be seen that the gas sensitivity of all gas sensors first increases with the increase of the operating temperature, reaches the maximum value at 250°C, and then begins to decrease with the increase of the operating temperature. At 250°C, the sensitivity of the comparative example is ~30, the sensitivity of Example 1 is ~35, the sensitivity of Example 2 is ~74, and the highest sensitivity of Example 3 is ~45. This shows that doping ZnO with an appropriate amount of Mg helps to construct a highly sensitive ethanol gas sensor;

[0030] Figure 5 This is the sensitivity curve of Example 2 at 250°C for different concentrations of ethanol gas. It can be seen that the sensitivity of the sensor to ethanol increases with the increase of gas concentration, the curve rises in a step-like manner, and the detection lower limit is 0.1ppm, and the sensitivity at this time is ~1.2;

[0031] Figure 6 The response recovery curve of the sensor prepared in Example 2 to 100 ppm ethanol gas at 250°C. It can be clearly seen that the sensor has a stable baseline resistance in air atmosphere and 100 ppm ethanol atmosphere. The sensor has a faster response time (5s) and a faster recovery time (98s). DETAILED DESCRIPTION

[0032] Comparative Example:

[0033] The pure phase ZnO porous hierarchical structure sensitive material is prepared by hydrothermal method to make a indirectly heated gas sensor. The specific production process is as follows:

[0034] (1) First, 1.488 g zinc nitrate hexahydrate (5 mmol), 0.6 g urea (10 mmol), and 3.3 g PVP K-30 were dissolved in 70 mL deionized water and stirred for 30 min;

[0035] (2) The homogeneous transparent solution in step (1) was placed into a 100 mL hydrothermal kettle, and the hydrothermal kettle was placed in an oven with the oven parameters set to: 150° C., 10 h;

[0036] (3) After the reaction is completed, the obtained white precipitate is washed alternately by centrifugation with deionized water and anhydrous ethanol for 6 times, and then the washed white precipitate is dried at 80°C for 24 hours, and then calcined in a muffle furnace. The muffle furnace parameters are set as follows: 500°C, 4 hours; the heating rate is 2°C / minute; a white powder is obtained, which is the ZnO porous hierarchical structure sensitive material, and the yield is about 1g;

[0037] (4) Take 10 mg of the calcined white powder and mix it with 0.1 mL of solvent (the volume ratio of anhydrous ethanol to deionized water is 1:1) to form a slurry. Use a brush to apply the slurry to the outer surface of the Al2O3 ceramic tube (there are two parallel ring-shaped gold electrodes separated from each other on the surface), so that the slurry is completely and evenly loaded on the gold electrode and the outer surface of the ceramic tube; the thickness is 20 μm; the inner diameter of the Al2O3 ceramic tube is 0.8 mm, the outer diameter is 1.2 mm, and the length is 4.0 mm; the width of the gold electrode is 0.40 mm, the distance between the two gold electrodes is 0.5 mm, and two folded platinum wires with a length of 5 mm are led out from each gold electrode;

[0038] (5) Place the coated ceramic tube in a muffle furnace for calcination at 400°C for 2 hours. After calcination, pass a nickel-chromium heating coil with a resistance of 35Ω through the interior of the Al2O3 ceramic tube. Control the current of the heating coil to provide the sensor with a suitable operating temperature. Finally, weld the four platinum wires of the sensor and the two ends of the heating coil to a hexagonal tube socket with indirect heating.

[0039] (6) The fabricated device was aged in an air environment at 200°C for 7 days, and finally a gas sensor of a pure phase ZnO porous hierarchical structure sensitive material was obtained.

[0040] Embodiment 1:

[0041] The 5at% MgO-ZnO porous hierarchical structure sensitive material was prepared by hydrothermal method to make a indirectly heated gas sensor. The specific production process is as follows:

[0042] (1) First, 1.488 g zinc nitrate hexahydrate (5 mmol), 0.6 g urea (10 mmol), 3.3 g PVP K-30 and 64 mg magnesium nitrate hexahydrate (0.25 mmol) were dissolved in 70 mL deionized water and stirred with a magnetic stirrer for 30 min;

[0043] (2) The homogeneous transparent solution in step (1) was placed into a 100 mL hydrothermal kettle, and the hydrothermal kettle was placed in an oven with the oven parameters set to: 150° C., 10 h;

[0044] (3) After the reaction is completed, the obtained white precipitate is washed alternately by centrifugation with deionized water and anhydrous ethanol for 6 times, and then the washed white precipitate is dried at 80°C for 24 hours, and then calcined in a muffle furnace. The muffle furnace parameters are set to: 500°C, 4 hours, and the heating rate is 2°C / minute; a white powder is obtained, which is the MgO-ZnO porous hierarchical structure sensitive material, and the yield is about 1g;

[0045] (4) Take 10 mg of the calcined white powder and mix it with 0.1 mL of solvent (the volume ratio of anhydrous ethanol to deionized water is 1:1) to form a slurry. Use a brush to apply the slurry to the outer surface of the Al2O3 ceramic tube (there are two parallel ring-shaped gold electrodes separated from each other on the surface), so that the slurry is completely and evenly loaded on the gold electrode and the outer surface of the ceramic tube; the thickness is 20 μm; the inner diameter of the Al2O3 ceramic tube is 0.8 mm, the outer diameter is 1.2 mm, and the length is 4.0 mm; the width of the gold electrode is 0.40 mm, the distance between the two gold electrodes is 0.5 mm, and two folded platinum wires with a length of 5 mm are led out from each gold electrode;

[0046] (5) Place the coated ceramic tube in a muffle furnace for calcination at 400°C for 2 hours. After calcination, pass a nickel-chromium heating coil with a resistance of 35Ω through the interior of the Al2O3 ceramic tube. Control the current of the heating coil to provide the sensor with a suitable operating temperature. Finally, weld the four platinum wires of the sensor and the two ends of the heating coil to a hexagonal tube socket with indirect heating.

[0047] (6) The fabricated device was aged in an air environment at 200° C. for 7 days, and finally a gas sensor based on 5at% MgO-ZnO porous hierarchical structure sensitive material was obtained.

[0048] Embodiment 2:

[0049] The 7at% MgO-ZnO porous hierarchical structure sensitive material was prepared by hydrothermal method to make a indirectly heated gas sensor. The specific production process is as follows:

[0050] (1) First, 1.488 g zinc nitrate hexahydrate (5 mmol), 0.6 g urea (10 mmol), 3.3 g PVP K-30 and 89 mg magnesium nitrate hexahydrate (0.35 mmol) were dissolved in 70 mL deionized water and stirred for 30 min;

[0051] (2) The homogeneous transparent solution in step (1) was placed into a 100 mL hydrothermal kettle, and the hydrothermal kettle was placed in an oven with the oven parameters set to: 150° C., 10 h;

[0052] (3) After the reaction is completed, the obtained white precipitate is washed alternately by centrifugation with deionized water and anhydrous ethanol for 6 times, and then the washed white precipitate is dried at 80°C for 24 hours, and then calcined in a muffle furnace. The muffle furnace parameters are set to: 500°C, 4 hours; the heating rate is 2°C / minute; a white powder is obtained, which is the MgO-ZnO porous hierarchical structure sensitive material, and the yield is about 1g;

[0053] (4) Take 10 mg of the calcined white powder and mix it with 0.1 mL of solvent (the volume ratio of anhydrous ethanol to deionized water is 1:1) to form a slurry. Use a brush to apply the slurry to the outer surface of the Al2O3 ceramic tube (there are two parallel ring-shaped gold electrodes separated from each other on the surface), so that the slurry is completely and evenly loaded on the gold electrode and the outer surface of the ceramic tube; the thickness is 20 μm; the inner diameter of the Al2O3 ceramic tube is 0.8 mm, the outer diameter is 1.2 mm, and the length is 4.0 mm; the width of the gold electrode is 0.40 mm, the distance between the two gold electrodes is 0.5 mm, and two folded platinum wires with a length of 5 mm are led out from each gold electrode;

[0054] (5) Place the coated ceramic tube in a muffle furnace for calcination at 400°C for 2 hours. After calcination, pass a nickel-chromium heating coil with a resistance of 35Ω through the interior of the Al2O3 ceramic tube. Control the current of the heating coil to provide the sensor with a suitable operating temperature. Finally, weld the four platinum wires of the sensor and the two ends of the heating coil to a hexagonal tube socket with indirect heating.

[0055] (6) The fabricated device was aged in an air environment at 200° C. for 7 days, and finally a gas sensor based on 7at% MgO-ZnO porous hierarchical structure sensitive material was obtained.

[0056] Embodiment 3:

[0057] The 9at% MgO-ZnO porous hierarchical structure sensitive material was prepared by hydrothermal method to make a indirectly heated gas sensor. The specific production process is as follows:

[0058] (1) First, 1.488 g zinc nitrate hexahydrate (5 mmol), 0.6 g urea (10 mmol), 3.3 g PVP K-30 and 115 mg magnesium nitrate hexahydrate (0.45 mmol) were dissolved in 70 mL deionized water and stirred for 30 min;

[0059] (2) The homogeneous transparent solution in step (1) was placed into a 100 mL hydrothermal kettle, and the hydrothermal kettle was placed in an oven with the oven parameters set to: 150° C., 10 h;

[0060] (3) After the reaction is completed, the obtained white precipitate is washed alternately by centrifugation with deionized water and anhydrous ethanol for 6 times, and then the washed white precipitate is dried at 80°C for 24 hours, and then calcined in a muffle furnace. The muffle furnace parameters are set to: 500°C, 4 hours; the heating rate is 2°C / minute; a white powder is obtained, which is the MgO-ZnO porous hierarchical structure sensitive material, and the yield is about 1g;

[0061] (4) Take 10 mg of the calcined white powder and mix it with 0.1 mL of solvent (the volume ratio of anhydrous ethanol to deionized water is 1:1) to form a slurry. Use a brush to apply the slurry to the outer surface of the Al2O3 ceramic tube (there are two parallel ring-shaped gold electrodes separated from each other on the surface), so that the slurry is completely and evenly loaded on the gold electrode and the outer surface of the ceramic tube; the thickness is 20 μm; the inner diameter of the Al2O3 ceramic tube is 0.8 mm, the outer diameter is 1.2 mm, and the length is 4.0 mm; the width of the gold electrode is 0.40 mm, the distance between the two gold electrodes is 0.5 mm, and two folded platinum wires with a length of 5 mm are led out from each gold electrode;

[0062] (5) Place the coated ceramic tube in a muffle furnace for calcination at 400°C for 2 hours. After calcination, pass a nickel-chromium heating coil with a resistance of 35Ω through the interior of the Al2O3 ceramic tube. Control the current of the heating coil to provide the sensor with a suitable operating temperature. Finally, weld the four platinum wires of the sensor and the two ends of the heating coil to a hexagonal tube socket with indirect heating.

[0063] (6) The fabricated device was aged in an air environment at 200° C. for 7 days, and finally a gas sensor based on 9at% MgO-ZnO porous hierarchical structure sensitive material was obtained.

Claims

1. A gas sensor based on MgO-ZnO porous hierarchical structure sensitive material, comprising an Al2O3 ceramic tube substrate with two parallel, annular and separate gold electrodes on the outer surface, a nano-sensitive material coated on the outer surface of the Al2O3 ceramic tube and the gold electrodes, and a nickel-chromium alloy heating coil placed in the Al2O3 ceramic tube; characterized in that: The nano-sensitive material is a MgO-ZnO porous hierarchical structure sensitive material, and is prepared by the following steps: (1) dissolving 5 mmol of zinc nitrate hexahydrate, 10 mmol of urea, 3.3 g of polyvinyl pyrrolidone and magnesium nitrate hexahydrate in 60-80 mL of deionized water, and stirring with a magnetic stirrer for 20-40 minutes; wherein the atomic ratio of magnesium to zinc is 0.05-0.10:1; (2) transferring the mixture solution obtained in step (1) into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, reacting at 140-160° C. for 8-15 hours; after naturally cooling to room temperature, washing the reaction product with deionized water and anhydrous ethanol by centrifugation alternately for 5-8 times, and then drying in an air atmosphere at 70-90° C. for 20-30 hours; (3) The product obtained in step (2) is heated to 450-550° C. at a heating rate of 2-3° C. / min in a muffle furnace, and then calcined for 3-5 hours to obtain a white powder, which is the MgO-ZnO porous hierarchical structure sensitive material.

2. A gas sensor based on MgO-ZnO porous hierarchical structure sensitive material as claimed in claim 1, characterized in that: The inner diameter of the Al2O3 ceramic tube is 0.7-0.9 mm, the outer diameter is 1.1-1.3 mm, and the length is 3.8-4.2 mm; the width of the gold electrode is 0.35-0.45 mm, the distance between the two gold electrodes is 0.4-0.6 mm, and two folded platinum wires with a length of 4-6 mm are led out from each gold electrode.

3. Application of a gas sensor based on the MgO-ZnO porous hierarchical structure sensitive material as described in claim 1 or 2 in detecting ethanol gas.

4. A method for preparing a gas sensor based on MgO-ZnO porous hierarchical structure sensitive material, the steps of which are as follows: (1) 5-15 mg of MgO-ZnO porous hierarchical structure sensitive material and 0.1-0.3 mL of a mixed solvent of anhydrous ethanol and deionized water in a volume ratio of 1:1 are uniformly mixed to form a slurry, and the slurry is applied to the outer surface of the Al2O3 ceramic tube substrate and the gold electrode with a brush to a thickness of 15-30 μm; (2) calcining the Al2O3 ceramic tube coated in step (1) at 350-450°C for 1.5-3.0h, then passing a nickel-chromium alloy heating coil with a resistance value of 30-40Ω through the interior of the Al2O3 ceramic tube, controlling the current passing through the heating coil so that the sensor operates at a suitable temperature, and finally welding the platinum wire of the sensor and both ends of the nickel-chromium alloy heating coil to a indirectly heated hexagonal tube socket; (3) Aging the device obtained in step (2) in an air environment at 180-220° C. for 6-8 days, thereby obtaining the gas sensor based on the MgO-ZnO porous hierarchical structure sensitive material.

Citation Information

Patent Citations

  • ZnO-based film and preparation method thereof

    CN103710675A

  • Method for preparing high-sensitivity low working temperature ethanol gas sensor element

    CN106018496A

  • High gas response and selective LaFeO3-based ethanol gas sensor element and preparation method thereof

    CN108205002A

  • Method for preparing magnesium-doped zinc oxide humidity-sensitive material by liquid phase

    CN108217714A

  • Preparation method of low-temperature working type high-performance ethanol gas sensor

    CN111077189A